Length of stay, mortality, and readmissions among Medicare cancer patients treated with glucarpidase and conventional care: a retrospective study - Demiralp B; Koenig L; Kala J; Feng C; Hamlett EG; Steele-Adjognon M; Ward S (Dove Medical Press, 2019)
Berna Demiralp,1 Lane Koenig,1 Jaya Kala,2 Chaoling Feng,1 Elizabeth G Hamlett,1 Marie Steele-Adjognon,1 Suzanne Ward3 1KNG Health Consulting, Rockville, MD, USA; 2University of Texas Health Science Center, University of Texas MD Anderson Cancer Center, Houston, TX, USA; 3BTG International, West Conshohocken, PA, USA Purpose: Glucarpidase (Voraxaze) is used to treat methotrexate (Mtx) toxicity in patients with delayed Mtx clearance due to impaired renal function. We examine hospital length of stay (LOS), mortality, and readmission rates for Medicare cancer patients with delayed clearance of Mtx treated with glucarpidase. Methods: Using 2010–2017 Medicare claims data, we identified glucarpidase patients as those hospitalized with indications of select lymphomas or leukemia, inpatient chemotherapy, and glucarpidase treatment. We assessed outcomes of glucarpidase patients relative to those experienced by patients treated for presumed Mtx toxicity using other therapies. These nonglucarpidase patients were identified with a diagnosis of primary central nervous system lymphoma, indications of cancer-chemotherapy toxicity, and acute kidney injury during hospitalization (not present on admission), and were divided into two groups: treated with dialysis (dialysis+) and treated with or without dialysis (dialysis+/–). Inverse-probability treatment weighting using propensity scores was used to adjust for differences between groups. Results: Patients treated with glucarpidase (n=30) had an average LOS of 14.7 days. They had inpatient, 30-day, and 90-day mortality rates of 3.3%, 13.3%, and 16.7%, respectively, and a 90-day all-cause unplanned readmission rate of 24.1%. The dialysis+ and dialysis+/– groups, respectively, had higher average LOS (40.2, 21.9), higher inpatient mortality (50.6%, 20.8%), and higher 90-day mortality (58.6%, 37.6%). No statistically significant differences in 30-day mortality or 90-day readmission rates were detected between the glucarpidase group and either of the nonglucarpidase groups. Unobservable differences in patient severity may impact the interpretation of our findings. Conclusion: Medicare cancer patients with presumed Mtx toxicity receiving conventional treatment experience long hospitalizations, high intensive-care unit use and high mortality. Glucarpidase patients had lower LOS, inpatient mortality, and 90-day mortality than the nonglucarpidase patients. Keywords: chemotherapy, toxicity, methotrexate, outcomes